2018
DOI: 10.5603/pjnns.a2019.0040
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of single- and multi-level anterior cervical discectomy and fusion with polyetheretherketone cages: radiological and clinical outcomes

Abstract: Objective. The aim of this study was to analyse the outcomes of single-and multi-level anterior cervical discectomy and fusion (ACDF) with standalone polyetheretherketone (PEEK) cages, with particular emphasis on the risk of secondary adjacent segment disease.Materials and methods. This retrospective study included 30 patients with single-or multi-level cervical disc herniation. Before the ACDF, and one year thereafter, the patients underwent clinical and radiological evaluation including determination of cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…This 3-month fusion rate (which persists also in the 12-month follow-up) compares well to long-term fusion rates published in several international studies with different cage materials and structures and the additional use of autologous bone or bone substitutes [ 33 , 35 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This 3-month fusion rate (which persists also in the 12-month follow-up) compares well to long-term fusion rates published in several international studies with different cage materials and structures and the additional use of autologous bone or bone substitutes [ 33 , 35 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 84%
“…The fusion rates of stand-alone PEEK cages range between 69 and 90% after 6 months or longer [ 24 , 33 35 ]. However, there is a great variability in the fusion rates as well as in the time span required for a complete and stable fusion [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, we have physiotherapists, neurologists and anaesthetists involved in treatment at pain clinics who conduct non-surgical treatments such as physical therapy, immobilisation with orthotics, medications, and spinal injections. On the other hand, there are orthopaedic surgeons and neurosurgeons performing spinal decompression surgery with anterior or posterior stabilisation anteriorly or posteriorly [28,29]. Some studies have suggested that surgical treatment may be more advantageous than non-operative treatment [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that surgical treatment may be more advantageous than non-operative treatment [30,31]. Patients in this group have shown improvements in pain and functional status, whereas patients who were managed non-operatively were able to perform fewer activities of daily living and had progressive worsening of neurological symptoms [29]. Another study by Bond et al [32] showed that patients treated surgically for mild cervical myelopathy did not differ from those treated conservatively with respect to baseline radiographic and demographic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Any deficits or dysfunction of these muscles may alter spinal biomechanics and heighten the risk of developing ASD early in the postoperative period 37 . Research has shown that ACDF increased the mobility of adjacent segment cephalic to the fused construct 38 . When some segments are fused, adjacent unfused segments need to increase mobility to compensate for the reduced range of motion, which may heighten the intradiscal pressure in adjacent discs and lead to development of ASD 39,40 .…”
Section: Discussionmentioning
confidence: 99%